Improving Students’ Vocabulary Through Paper-Mode Quizizz: A Classroom Action Research in Indonesian EFL setting - Rizal Wahid Permana Putra (English Learning Innovation (englie), 2023)
Vocabulary is an essential component in learning a second or a foreign language. It is one of the most important aspects of obtaining all four language skills; reading, listening, speaking, and writing. Therefore, teaching and learning vocabulary should be done through various-interactive media so that children are interested in acquiring it. Integrating gamefication-based learning media can be utilised to support the teaching-learning vocabulary. In addition, Paper-Mode Quizziz can be used as a game-based learning platform offering multiple tools to make a classroom fun, interactive, and engaging in learning vocabulary. This research aimed at investigating the use of Paper-Mode Quizizz to improve students’ vocabulary at eighth grade students. This research was Classroom Action Research conducted at eighth grade students. The research subject was 8C grade students of SMP SSA Negeri Kloposawit 1 Candipuro. Further, this research was conducted in two cycles. In cycle I, the researcher found that the eighth-grade students’ vocabulary mastery was improved. The average score was 72,4. Further, in cycle II, the eighth-grade students’ vocabulary mastery was much better than in cycle II. the average score was 81,4. It showed that the use of Paper-Mode Quizizz profoundly improved the eighth-grade students’ vocabulary mastery. In addition, the students were more enjoyed, actively participated, highly motivated, and engaged with the use of Paper-Mode Quizizz in learning new vocabularies. In short, the implementation of Paper-Mode Quizizz profoundly improved the students’ vocabulary mastery at eighth-grade students in learning English.